Effect of Al-Cu Bimetallic Components in a TiO2 Framework for High Hydrogen Production on Methanol/Water Photo-Splitting - A-Young Kim; Misook Kang (International Journal of Photoenergy)
This study investigated the production of hydrogen over TiO2, Cu-TiO2, Ag-TiO2, and Cu-Ag-TiO2 photocatalysts incorporated with Cu and Ag ions by a solvothermal method. The Ag metal (200, 220, and 311 plane) peaks at 2𝜃=44.50, 64.00, and 77.60o were presented in the Ag-incorporated TiO2 catalysts. The CuO component (Cu2p3/2 and Cu2p1/2 at 930.4 and 949.5 eV) was exhibited in the X-ray photon spectroscopy (XPS) band of the Cu-incorporated TiO2 photocatalyst. All the absorption plots in the Cu-, Ag-, and Cu-Ag-incorporated catalysts showed excitation characteristics; an asymmetric tail was observed towards a higher wavelength due to scattering. The intensity of the photoluminescence (PL) curves of Cu-Ag-TiO2s was smaller, with the smallest case being observed for Cu(0.05)-Ag(0.05)Ti(0.9)O2 and Cu(0.03)-Ag(0.07)Ti(0.9)O2. Based on these optical characteristics, the production of H2 from methanol/water photodecomposition over the Cu(0.03)-Ag(0.07)Ti(0.9)O2 photocatalyst at 8,750 mmol after 8 h was greater than that over the other photocatalysts.